2015
DOI: 10.14338/ijpt-15-00011.1
|View full text |Cite
|
Sign up to set email alerts
|

Proton Therapy Reduces Treatment-Related Toxicities for Patients with Nasopharyngeal Cancer: A Case-Match Control Study of Intensity-Modulated Proton Therapy and Intensity-Modulated Photon Therapy

Abstract: Purpose: The physical properties of proton therapy allow for decreased dose delivery to nontarget structures. The purpose of this study was to determine if this translates into a clinical benefit by comparing acute and chronic morbidity between patients with nasopharyngeal carcinoma who are treated with intensity-modulated proton therapy (IMPT) and those treated with intensity-modulated radiation therapy (IMRT). Materials and Methods: Patients receiving IMPT for nasopharyngeal cancer from 2011-13 were matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 34 publications
(40 reference statements)
10
96
1
1
Order By: Relevance
“…33 It stands to reason that patients with OPC may similarly benefit, and, indeed, preliminary findings also show an approximately 50% reduction in feeding tube insertion rates for patients with OPC undergoing IMPT compared with historical control patients treated with IMRT. 34 Analyses are currently ongoing for a contemporary case-matched cohort study.…”
Section: Structuresmentioning
confidence: 90%
“…33 It stands to reason that patients with OPC may similarly benefit, and, indeed, preliminary findings also show an approximately 50% reduction in feeding tube insertion rates for patients with OPC undergoing IMPT compared with historical control patients treated with IMRT. 34 Analyses are currently ongoing for a contemporary case-matched cohort study.…”
Section: Structuresmentioning
confidence: 90%
“…The average volume of PTV in the present study was 134.94 6 34.44 cm 3 . D 95% reported was 20.08 6 0.06 Gy, 20.1 6 0.04…”
Section: Target Volume Coveragementioning
confidence: 45%
“…While the opposed parallel pair geometry should help offset this uncertainty, the authors estimated variability by forcing the density of the bowel in the field to 0.5 g/cm 3 , which is a first-order estimate of the potential range of the different scenarios. Photon plans were designed on the Varian Eclipse Treatment Planning System, version 11.0 (Varian Medical System Inc, Palo Alto, California), with 6-MV flattening filter free photon beams from a Varian True Beam equipped with high definition multileaf collimator.…”
Section: Patient Simulation and Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the toxicity story may not be that simple. For example, in a meta-analysis of observational studies in nasal cavity/paranasal sinus cancer, the rate of neurological toxicity was significantly higher with charged particle therapy than with photon therapy (0.2 vs 0.04, respectively, PZ.0002) (1), and the MD Anderson retrospective casecontrol study in nasopharyngeal cancer patients showed a doubling of temporal lobe necrosis with PBT versus that with photon therapy (2 of 10 vs 2 of 20 patients, respectively, P value not given) (2). Because coverage and avoidance compromises are required even in PBT planning, it is possible that PBT dose distributions may exchange certain toxicities related to the intensity modulated radiation therapy IMRT "low-dose bath" (eg, loss of hair or taste) for others related to increased dose heterogeneity (3) or planning and delivery inaccuracies at critical tissue interfaces.…”
mentioning
confidence: 99%